The Influence of eWOM Purchase Intention with Trust Mediating Variables on MOP Beauty Product - Gea Aprinda Santyadewi; Albari Albari (Universitas Trunodjoyo Madura, 2024)
This research aims to determine the effect of Electronic Word of Mouth (eWOM) on purchasing intensity and trust as a mediating variable with the research object Mother of Pearl (MOP) Beauty. The sampling method used was convenience sampling, the sample used involved 280 e-commerce users who were familiar with the MOP Beauty brand. Data was collected and analyzed using Structural Equation Modeling (SEM) via SmartPLS software. The research results show that there is a positive influence of information quality, information quantity, information credibility on trust, while information usefulness has a negative influence on trust. Furthermore, trust, information quality, information credibility, information usefulness have a positive influence on purchase intention, while information quantity shows no positive influence on purchase intention. This research can contribute to understanding the role of eWOM and trust in the context of purchasing cosmetic products, especially the MOP Beauty brand, so that they pay attention to and utilize eWOM as an effective marketing tool, while strengthening consumer trust in the brand. Based on the background discussed, this research aims to analyze the relationship between eWOM and purchase intention. However, different from previous studies, this research adds trust as a mediating variable in the relationship between the dependent and independent variables. Choosing the research object Mother of Pearl Beauty is because it is a cosmetic product owned by influencer Tasya Farasya, which is one of the cosmetic brands that has the most sales in Indonesia.